Effect of ruminal ammonia supply on lysine utilization by growing steers - Hussein, A. H.; Batista, E. D.; Miesner, M. D.; Titgemeyer, Evan C. (My University, 2016)
Six ruminally cannulated Holstein steers (202 +/- 15 kg) were used to study the effects of ruminal ammonia loading on whole-body lysine (Lys) utilization. Steers were housed in metabolism crates and used in a 6 x 6 Latin square design. All steers received 2.52 kg DM/d of a diet (10.1% CP) containing 82% soybean hulls, 8% wheat straw, 5% cane molasses, and 5% vitamins and minerals, and 10 g/d of urea (considered to be part of the basal diet) was ruminally infused continuously to ensure adequate ruminal ammonia concentrations. All steers were ruminally infused continuously with 200 g/d of acetic acid, 200 g/d of propionic acid, and 50 g/d of butyric acid and abomasally infused with 300 g/d of glucose continuously to increase energy supply without increasing microbial protein supply. Steers were also abomasally infused continuously with an excess of all essential AA except Lys to ensure that Lys was the only limiting AA. Treatments were arranged as a 3 x 2 factorial with 3 levels of urea (0, 40, or 80 g/d) continuously infused ruminally to induce ammonia loading and 2 levels of Lys (0 or 6 g/d) continuously infused abomasally. Treatments did not affect fecal N output (P = 0.37). Lysine supplementation decreased (P < 0.01) urinary N excretion from 51.9 g/d to 44.3 g/d, increased (P < 0.01) retained N from 24.8 to 33.8 g/d, increased (P < 0.01) plasma Lys, and decreased (P <= 0.05) plasma serine, tyrosine, valine, leucine, and phenylalanine. Lysine supplementation also tended (P = 0.09) to reduce plasma urea-N. Urea infusions linearly increased (P = 0.05) retained N (27.1, 29.3, and 31.5 g/d) and also linearly increased (P < 0.01) urinary N excretion (31.8, 48.1, and 64.4 g/d), urinary urea (21.9, 37.7, and 54.3 g/d), urinary ammonia (1.1, 1.4, and 1.9 g/d), and plasma urea (2.7, 4.0, and 5.1 mM), and linearly decreased plasma alanine (P = 0.04) and plasma glycine (P < 0.01). Assuming that retained protein is 6.25 x retained N and contains 6.4% Lys, the incremental efficiencies of infused Lys utilization were 51%, 59%, and 69% for steers receiving 0, 40, and 80 g/d of urea, respectively, indicating that ruminal ammonia loads may improve the efficiency of Lys utilization. This is supported by observed increases in whole body-protein deposition in response to ammonia loading of our steers that were, by design, Lys deficient.
Citation: Hussein, A. H., Batista, E. D., Miesner, M. D., & Titgemeyer, E. C. (2016). Effect of ruminal ammonia supply on lysine utilization by growing steers. Journal of Animal Science, 94(2), 656-664. doi:10.2527/jas2015-9717
Keywords: Amino Acid; Cattle; Growth; Lysine; Utilization; Amino-Acid Utilization